Impact of prebiopsy magnetic resonance imaging on biopsy and radical prostatectomy grade concordance. Issue 13 (22nd April 2020) - Shoag, Jonathan E.; Cai, Peter Y.; Gross, Michael D.; Gaffney, Christopher; Li, Dongze; Mao, Jialin; Nowels, Molly; Scherr, Douglas S.; Sedrakyan, Art; Hu, Jim C.
Abstract : Background: Adoption of prostate magnetic resonance imaging (MRI) before biopsy is based on evidence demonstrating superior detection of clinically significant prostate cancer on biopsy. Whether this is due to the detection of otherwise occult higher grade cancers or preferential sampling of higher grade areas within an otherwise low‐grade cancer is unknown. Methods: To distinguish these two possibilities, this study examined the effect of prebiopsy MRI on the rate of pathologic upgrading and downgrading at prostatectomy in Surveillance, Epidemiology, and End Results–Medicare linked data from 2010 to 2015. Logistic regression was performed to assess the effect of MRI use on the Gleason grade change between biopsy and prostatectomy. Results: Among biopsy‐naive men, those who underwent prebiopsy MRI had higher odds of downgrading at prostatectomy (odds ratio [OR], 1.32; 95% confidence interval [CI], 1.05‐1.66). In contrast, the odds of upgrading were significantly lower for men who underwent prebiopsy MRI (OR, 0.78; 95% CI, 0.61‐0.99). Limitations included a low overall rate of MRI‐utilization prior to biopsy and an inability to distinguish between template, software‐assisted and cognitive fusion biopsy. Conclusions: Prebiopsy MRI is associated with both oversampling of higher grade areas, which results in downgrading at prostatectomy, and the detection of otherwise occult higher grade lesions, which results in less upgrading at prostatectomy. Abstract : A nationally representative, population‐based cohort is used to show significantly greater odds of downgrading and lower odds of upgrading at radical prostatectomy when prebiopsy magnetic resonance imaging is performed. This suggests that magnetic resonance imaging allows for the selective sampling, including oversampling, of high‐grade prostate cancers.